ASEAN-China Free Trade Area and the Competitiveness of Local Industries: A Case Study of Major Industries in the Lao People's Democratic Republic - Leebeer Leebouapao; Sthabandith Insisienmay; Vanthana Nolintha (Asian Development Bank (ADB), 2012)
This paper provides an evaluation of the impact of the ASEAN-China Free Trade Agreement (ACFTA) on industries in the Lao People's Democratic Republic (Lao PDR). In general, the paper finds that price competitiveness in the three industries under review falls substantially if tariffs are completely removed. However, the degree of impact varies substantially across industries. In the wood processing and cement industries, of which the latter benefits from import substitution policies, competitiveness based on both price and product quality will be affected by the removal of tariffs. Ensuring product quality in the face of increased competition from neighboring countries will be crucial for both industries in order to maintain domestic market share and expand into ASEAN and People's Republic of China (PRC) markets. For a foreign direct investment (FDI)-led industry such as motorcycle assembly, the concern over price competitiveness seems to be less significant. However, strengthening product quality and brand reputation should be high on the agenda of Lao People's Democratic Republic motorcycle assemblers as they seek to penetrate the neighboring Thai market. This paper concludes by recommending a package of industry-specific policy interventions to prepare Lao People's Democratic Republic industries for increased competition in domestic markets and possible expansion into the more competitive regional markets of ASEAN and the People's Republic of China.
hdl:11540/1301
Keywords: F15; 330; ACFTA; FTA; Laos; Lao Peoples Democratic Republic; ASEAN; Peoples Republic of China; Free Trade Area; Freihandelszone; ASEAN-Staaten; Internationaler Wettbewerb; Produktionsstandort; Industrie; Laos